DEMPLOT INISIASI PRODUKSI BENIH BEBERAPA VARIETAS PADI LOKAL PADA KELOMPO TANI MEKAR BARU DI DESA WAIMITAL KABUPATEN SERAM BAGIAN BARAT - Kesaulya, Henry; Laisina, Jane J.K.; Patrouw, Jopy; Devinubun, Fatima (Universitas Pattimura, 2023)
The demonstration plot for the initiation of seed production for several local rice varieties from Maluku in Waimital Village, West Seram Regency is a form of community service. The use of superior quality seeds has an effect on increasing rice productivity. The results of the problem analysis found several problems, including local rice seed production techniques, knowledge and provision of certified local rice seeds that had not been mastered by farmers. Evaluation of the success of the demonstration plot at each stage is carried out, including initial evaluation and process evaluation. The approach to implementing production initiation demonstration plots in community service influences the success of implementing local rice seed production technology initiation. There has been an increase in the percentage of changes in mastery of technology, skills, mastery of local rice seed production procedures and techniques and the change process that occurs is based on the knowledge and experience farmers have previously had so that the change process does not experience difficulties.